Food and nutrition security and the eradication of hunger CELAC 2025 : furthering discussion and regional cooperation (ECLAC SantiagoCL, 2016)
Aims to provide the region's countires with up-to-date and timely information on the status of food and nutrition security; on the rolde of eradicating hunger played by the different areas such as agriculture, agrifood trade and natural resources management; and on the possibility of successfully addressing the twin burden of malnutrition, in a context where the effects of climate change could threaten the progress achieved in Latin America and the Caribbean thus far.
Keywords: FOOD SECURITY